Seeking An African Solution For Equity And Inclusion: The African Continental Publishing Platform - Raju, Reggie; Claassen, Jill (My University, 2023)
This presentation was delivered at Open Repositories 2023 Conference as part of Panel 7: LIBSENSE Africa - Breaking down silos across infrastructures to improve the visibility of African research outputs
Keywords: Equity & Inclusion; Publishing Platform; Journals